Design of Cashew Marketing Strategy Through Evaluation of Export Potential to Enter the Global Market (Case Study of Mrs. Tini's MSMEs in Ciputat) - Revikhansyah, Thiersyanda (Jurnal Multidisiplin Indonesia, 2024)
This study aims to identify market expansion opportunities and address the administrative barriers MSMEs Kacang Mete Bu Tini face in exporting fresh or dried shelled cashew nuts with HS Code 080132 to Malaysia and Thailand. MSMEs Kacang Mete Bu Tini encounter significant administrative obstacles due to the lack of essential export documents such as quality certificates, certificates of origin, etc. These obstacles slow the market expansion and reduce the product's competitiveness in international markets. The research conducted through Revealed Comparative Advantage (RCA) analysis shows that Indonesian cashew nuts have significant comparative advantages in the Malaysian and Thai markets, with RCA values reaching 3.318911 in Malaysia and 2.556656 in Thailand. An RCA value greater than one indicates a comparative advantage in both markets. Regarding competitive advantage, Malaysia holds a "Rising Star" position with an annual export market share growth of 0.281030 percent and a cashew market growth of 0.180204 percent per year. In contrast, Thailand is in a "Retreat" position with an annual export market share growth of -0.509915 percent and a cashew market growth of -0.009638 percent per year, indicating a decline in demand and less satisfactory export performance. The conclusion is that Malaysia is a more suitable export destination for Cashew Nut Bu Tini MSMEs, given the higher RCA value and more favorable market position. MSMEs Kacang Cashew Bu Tini needs to promptly complete the necessary administrative documents to enhance product competitiveness and expand export markets.